2020
DOI: 10.1002/aoc.5696
|View full text |Cite
|
Sign up to set email alerts
|

Ligational, DFT modeling and biological properties of some new metal complexes with 3‐(bromoacetyl)coumarin and 1,10‐phenanthroline

Abstract: The synthesis and characterization of Mn (II), Fe (II), Co (II), Ni (II), Cu (II) and Zn (II) complexes with 3-(bromoacetyl)coumarin (BAC) in presence of 1,10-phenanthroline (Phen) were reported and described by elemental analysis, molar conductivity, FT-IR, UV-Vis and effective magnetic moments. TG and DTG have been applied to study the decomposition mechanisms for BAC, Phen and their complexes. The analytical results and spectral studies showed that BAC and Phen act as bidentate ligands via oxygen of α, β-un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…The new bands, in the range 500–528 nm, found in the complexes may be assigned to ligand-metal charge transfer [ 8 , 35 , 36 , 37 , 38 , 39 ]. The two bands found at 570 and 610 nm in absorbance spectrum of ( A ) complex may be assigned to 6 A1→ 4 T 2 (G) and 6 A 1g → 4 T 2g (4G) transition, respectively [ 16 ] For ( B ) complex, showing absorption band at 605 nm which may be assigned to 6 T 1g (F)→ 4 T 1g (P) transition, suggest that there is an octahedral geometry around Co(II). For ( C ) complex, the observed band at 600 nm refers to 3 A 2g → 3 T 1g (P) transition which supports distorted octahedral geometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new bands, in the range 500–528 nm, found in the complexes may be assigned to ligand-metal charge transfer [ 8 , 35 , 36 , 37 , 38 , 39 ]. The two bands found at 570 and 610 nm in absorbance spectrum of ( A ) complex may be assigned to 6 A1→ 4 T 2 (G) and 6 A 1g → 4 T 2g (4G) transition, respectively [ 16 ] For ( B ) complex, showing absorption band at 605 nm which may be assigned to 6 T 1g (F)→ 4 T 1g (P) transition, suggest that there is an octahedral geometry around Co(II). For ( C ) complex, the observed band at 600 nm refers to 3 A 2g → 3 T 1g (P) transition which supports distorted octahedral geometry.…”
Section: Resultsmentioning
confidence: 99%
“…Peptides with a higher proportion of Gly were generally less potent and caused less bacterial membrane alteration, as observed by flow cytometry and AFM, which correlate to structural characteristics as observed by circular dichroism spectroscopy and predicted by molecular dynamics’ calculations [ 10 , 11 , 12 ]. It is important to highlight there are limited reports about metal complexes with H 2 mel and Gly [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 42 ] Also, the peaks at δ = 6.47–6.94 ppm may be attributed to –HC=N aliphatic and a multiplet at δ = 7.01–8.86 ppm to –CH aromatic. [ 1 ] Comparing the main signals of the complexes with those of free L, the 1 H NMR spectra of the complexes showed that the chemical shift values were only slightly changed compared with those of the free L due to the coordination of L with metal ions. Also, the 1 H NMR spectra of the complexes exhibited a new signal in the range of 3.30–4.07 ppm due to the presence of water molecules in the complexes.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent decades, tremendous research has been done on nitrogen and oxygen donor ligands as they possess both hard and soft bases with a variable coordination; they have also exhibited a significant biological efficacy against many microorganisms. [ 1–3 ] Schiff bases are one of the different potential sites that have wide applications in many fields such as food industry, dry industry, catalysis, fungicidal, agrochemical, optical, electrosensors, chromatographic methods, and biological activities and are also used as antituberculosis, DNA binding, and cleaving agents because of the presence of the chelating azomethine group. On the contrary, the transition metal complexes are used for the synthesis of cancer‐combating nonradioactive tools for chemotherapy and diagnosis and are also used in supramolecular photochemistry and in medicine.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, a PYE‐UNICAM SP 1900 atomic absorption spectrometer fitted with the corresponding lamp was used. [ 22 ] Using a Perkin‐Elmer 1430 ratio recording infrared spectrophotometer, the infrared spectra of the Schiff base and its metal complexes were recorded from (KBr discs) in the range of 4000–400 cm −1 . On the Varian Mercury VX‐300 NMR Spectrometer, 1 H‐NMR spectra were reported using DMSO‐d 6 as a solvent.…”
Section: Methodsmentioning
confidence: 99%